FENOMENOLOGI KECEMASAN LANSIA MENGHADAPI KEMATIAN DALAM PERSPEKTIF KEBUTUHAN SPIRITUAL DI DESA PODOROTO KECAMATAN KESAMBEN KABUPATEN JOMBANG - Hamid, Ikhwan; Priharninuk, Devin; Zakaria, Achmad (Jurnal EDUNursing, 2020)
AbstractElderly feel anxious in the face of death caused by elderly negative perception of death. It is necessary to approach the need to seniors such as spiritual needs approaches. Spiritual necessity is something that need by people to prepare for death. The design of the research used was qualitative research by phenomenological approach. Social situation is older people Ds Podoroto Kec Kesamben Kab Jombang. The informant was 4 elderly using the Snowball Sampling technique. This research Instrument used the interview guidelines that have been made, the collection data was done by interview. Data analyzed by using the Colaizzi methode. This research produces 4 themes namely theme 1 obtained from the sub theme reminds oneself then found the theme of preparing death. Theme 2 obtained from a sub theme inner proximity then found the theme felt close to God. Theme 3 obtained from the sub theme requires God from the sub theme found the theme of running the command of God. Theme 4 obtained from the sub theme lightens the load then found the theme provides benefits. Spiritual need for the elderly is a provision in the face of death, by doing worship to God. The activity has a positive effect that is feeling close to God so it is quieter in living life, preparing his death. The spiritual activities undertaken by the elderly are carried out continuously, which is the responsibility of the human being. Spiritual needs relate to the meaning of the elderly life is a form of interpersonal relationships between humans and others to provide mutual benefits.Keywords: Death, Elderly, SpiritualÂ